Strategic parenting, birth order, and school performance - Hotz, V. Joseph (J Popul Econ, 2015)
Fueled by new evidence, there has been renewed interest about the effects of birth order on human capital accumulation. The underlying causal mechanisms for such effects remain unsettled. We consider a model in which parents impose more stringent disciplinary environments in response to their earlier-born children’s poor performance in school in order to deter such outcomes for their later-born offspring. We provide robust empirical evidence that school performance of children in the National Longitudinal Study Children (NLSY-C) declines with birth order as does the stringency of their parents’ disciplinary restrictions. When asked how they will respond if a child brought home bad grades, parents state that they would be less likely to punish their later-born children. Taken together, these patterns are consistent with a reputation model of strategic parenting.